Web-based Conferencing: Tips, Tricks, and Scenario-based Best Practices for Clinicians During a Pandemic Crisis. Issue 4 (July 2020) - Catanzano, Tara M.; Nandwana, Sadhna B.; Folio, Les R.
Abstract : Abstract: This article will familiarize the reader with useful tools and trouble-shooting tips for web-based conferencing. Radiology-based scenarios for web conferencing are also provided.